Effect of cystic fibrosis transmembrane conductance regulator modulators and dedicated cystic fibrosis gastrointestinal clinic visits on the incidence of distal intestinal obstructive syndrome in persons with cystic fibrosis - Nicha Wongjarupong; Malique F. Delbrune; Jameel Alp; Daphne M. Moutsoglou; Talia Wiggen; Ashley Benner; Joanne L. Billings; Jordan M. Dunitz; Sarah J. Schwarzenberg; Baharak Moshiree; Shahnaz Sultan (PLoS ONE, 2025)
Background Gastrointestinal (GI) complications are the second most common disorders in persons with cystic fibrosis (PwCF). There is limited data on how having a dedicated CF-GI clinic and cystic fibrosis transmembrane conductance regulator (CFTR) modulators may affect rates of GI complications. Our aim was to assess the effect of the CF-GI clinic and CFTR modulators on GI complications with incidence of distal intestinal obstructive syndrome (DIOS). Methods This was a retrospective study of adult PwCF who were seen in a CF-GI clinic from 2000–2023. Comparisons were made between the numbers of admissions and emergency department (ED) visits for DIOS at three years before and after CFTR modulator use and the first CF-GI clinic visit. Results Of the 1,076 PwCF identified, 242 were seen in CF-GI clinic. Of this, 126 (52.1%) were female, with a median age of 40 (IQR: 30–47) years. There were 146 (60.3%) with regular use of laxatives. Of the 59 PwCF with CF-GI clinic visits for constipation, hospital admissions decreased in 16, were unchanged in 32, and increased in 11 (p = 0.402) while ED visits decreased in 9, remained the same in 40, and increased in 10 (p = 0.862). Of the 125 PwCF with CFTR modulator use, DIOS-related hospital admissions decreased in 15 patients, remained unchanged in 89, and increased in 21 (p = 0.021) while ED visits were fewer in 8, unchanged in 97, and increased in 20 (p = 0.587). Conclusion PwCF had high burden of constipation with a majority of patients regularly using laxatives, and almost half had a history of DIOS. CFTR modulator use and CF-GI clinic were not associated with a decrease of DIOS incidence.